Interaction Studies of Moxifloxacin with Anti-diabetic Drugs and Application of RP-HPLC in Analysis - Bashir, Sania; Qamar, Fatima; Naveed, Safila; Zainab, Syeda; Sadia, Halima; Sana, Aisha; Muzafar, Wajeeha (Indian Journal of Pharmaceutical Education and Research, 2023)
Aim: Simple RP-HPLC method was developed and validated for the simultaneous estimation of Glimepiride, Glibenclamide and Moxifloxacin in pharmaceutical preparation. Materials and Methods: Mediterranean C18 column with dimensions of 150mm×4.6mm was used with HPLC Shimadzu LC-20 AT model, Version 1:62 is used for processing of chromatograms at room temperature (25± 2°C). 1 mL per minute was the flow rate and detector were set at 254nm with mobile Phase consisting of 85:10:5 v/v methanol: water: acetonitrile. Results: The developed method proved to be accurate, simple, effective precise and reproducible. One way ANOVA was also applied for further confirmation of the results. Conclusion: The method is applicable for the routine analysis of drugs in API and in formulation and for studying in vitro interaction studies.
Keywords: Moxifloxacin; Glimepiride; Glibenclamide; in vitro interaction studies